Symptoms and ECG changes precede sudden cardiac death in hypertrophic cardiomyopathy-A nationwide study among the young in Sweden. - Erik Börjesson; Bodil Svennblad; Aase Wisten; Mats Börjesson; Eva-Lena Stattin (PLoS ONE, 2022)
Background Hypertrophic cardiomyopathy (HCM) is a major cause of sudden cardiac death (SCD) in the young. We aimed to characterize detailed family history, symptoms, hospital utilization and ECG changes before SCD. Methods We extracted all cases suffering SCD with HCM from the SUDDY cohort, which includes all cases of SCD between 2000-2010 in Sweden among individuals aged 0-35 years along with their controls. We gathered data from mandatory national registries, autopsy reports, medical records, ECGs (including military conscripts), and detailed family history from an interview-based questionnaire (with relatives, post-mortem). Results Thirty-eight cases (7 female), mean age 22 years, with HCM were identified. Among these, 71% presented with possible cardiac symptoms (chest pain [26%], syncope [22%], palpitations [37%]), before death; 69% received medical care (vs 21% in controls) within 180 days before death. The majority (68%) died during recreational activity (n = 14) or exercise/competitive sports (n = 12). Fifteen (39%) had a known cardiac disorder prior to death, with HCM being diagnosed pre-mortem in nine cases. 58% presented with abnormal ECG recordings pre-mortem, and 50% had a positive family history (1st-3rd generation) for heart disease. Conclusion In this comprehensive, nationwide study of SCD due to HCM, 87% (33/38) of cases had one or more abnormality prior to death, including cardiac symptoms, a positive family history, known cardiac disease or ECG abnormalities. They sought medical care prior death, to a larger extent than controls. These findings suggest that cardiac screening should be expanded beyond competitive athletes to aid SCD prevention in the young population with HCM.